(untitled) (Journal of Interdisciplinary Insights, 2026)
Urtyn duu is directly related to the noble customs and rituals of Mongolians such as state ceremonies, festivals, and weddings. It is a traditional art that was born from the life of nomadic Mongolians, sung in the Mongolian language, and has been passed down with great respect until now. In recognition of the wonders of Mongolian urtyn duu, in 2003, UNESCO declared Mongolian urtyn duu as a “Masterpiece of the Oral and Intangible Heritage of Humanity” and in 2008, it was registered on the “Intangible Cultural Heritage of Humanity” list.Urtyn duu is the art of singing long songs in a long-winded manner, using the breath, vocal organs, and larynx to create various vowel decorations, making them melodious, melodious, melodious, and melodious.The long song is a classic form of Mongolian folk song, and when compared to the characteristics of folk songs around the world, it is very unique and strange, a cry of the mountains and lands of Mongolia. There is almost no work that has not touched on the long song in the research conducted by foreign and domestic scholars on the traditional Mongolian singing art and musical culture.